Blockchain sharding storage scheme based on concatenated coding - TIAN Youliang; HUANG Yuqing; WANG Shuai (Tongxin xuebao)
Traditional blockchain faces the challenge of storage scalability. Existing research has reduced the storage overhead of blockchain based on erasure coding theory, but it brings high computational and communication spending during the decoding and recovery of blocks. To solve these problems, a blockchain sharding storage scheme based on concatenated coding was proposed. By adding a pre-coding layer to improve the existing rateless erasure code, a decoding complexity of <alternatives>Ο<mfenced separators="|">n</mfenced> <?fx-imagestate width="6.94266701" height="3.21733332"?> <?fx-imagestate width="6.94266701" height="3.21733332"?> </alternatives> was achieved. Considering the communication delay skew between nodes during the decoding process, a delay-sensitive sharding algorithm based on Metis was proposed, which cut down the communication expenditure in the decoding process by delaying weights to determine the shard ownership of nodes. Simulation results show that the proposed scheme not only ensures the reliability of blockchain data, but also has lower computational and communication cost compared to traditional schemes.